Direct Flux-Vector Control of Stand-Alone DFIG-Based Wind Energy Conversion System - Fella Boucetta; Mohamed Toufik Benchouia; Mohamed Becherif; Mohamed Chebani (Proceedings)
This article presents direct flux-vector control (DFC), a new control strategy based on direct torque control (DTC), for a doubly fed induction generator (DFIG) driven by wind, feeding AC loads without grid access [...]